Faktor-faktor yang Berhubungan dengan Pemberian Imunisasi Campak pada Balita - Sevilla Ukhtil Huvaid; Yulianita Yulianita; Nola Mairoza (Jurnal Riset Hesti Medan, 2019)
Measles immunization is complete basic immunization that must be given to children from 9 to 59 months. Measles immunization coverage in the Limau-Limau Posyandu at the Asam Kumbang Health Center has decreased from 69.2% to 41.9%. The purpose of this study was to determine the relationship between knowledge, attitudes, and roles of cadres and measles immunization in infants. This study uses a cross sectional approach. The population in this study were all mothers with children (9-59 months). The sample is all toddlers, while the respondents are all mothers who have toddlers with a total sampling technique. Analysis was performed using Chi Square test. The univariate results in this study indicate that more respondents did not bring their children for measles immunization (59.5%) more than half of respondents had low knowledge (64.9%), more than half of respondents were negative (62.2%), and more of half of respondents said the cadre's role was not good (62.2%) for measles immunization in infants. Bivariate results showed that there was a significant relationship between knowledge, attitudes and roles of cadres and measles immunization for infants (p = 0,000). For this reason, it is necessary to increase the frequency of counseling and training of cadres in order to change the role of cadres from less good to better, in addition respondents respondents must increase active participation in extension activities in order to increase knowledge.